The relationship between episodic detail generation and anterotemporal, posteromedial, and hippocampal white matter tracts. (February 2020) - Memel, Molly; Wank, Aubrey A.; Ryan, Lee; Grilli, Matthew D.
Abstract: Episodic details populate autobiographical memories with vivid representations of people, objects, and event happenings, and they link events to a specific time and place. Episodic detail generation is believed to be a function of medial temporal lobe (MTL)-cortical interaction, but much remains unclear about how this retrieval process unfolds. In the present study, we combined an autobiographical interview and diffusion magnetic resonance imaging to investigate the relationships of two types of episodic detail, namely details about entities of an event (people and objects) or "event elements" and details about spatiotemporal context, to the integrity of anterotemporal (uncinate fasciculus; UF) and posteromedial (cingulum bundle; CB) cortical pathways. We also measured the relationships of these detail types to the fornix, and the relationship between non-episodic details and these tracts. We found that only episodic detail generation was significantly related to cortical and hippocampal pathways. Notably, the UF was more strongly related to event element details than it was to spatiotemporal context details. In contrast, CB was significantly and similarly related to the generation of event element and spatiotemporal context details (when not controlling for age and global diffusion). The fornix was also significantly related to both types of episodic detail, although the relationship to spatiotemporal context was particularly robust. These findings support the idea that anterotemporal cortical regions are related to the retrieval of episodic details about the entities that are incorporated into autobiographical events. Our findings also align with the notion that posteromedial and hippocampal-cortical involvement support the retrieval of episodic details.